2019
DOI: 10.1016/j.chroma.2019.02.006
|View full text |Cite
|
Sign up to set email alerts
|

High-performance thin-layer chromatography/bioautography and liquid chromatography-mass spectrometry hyphenated with chemometrics for the quality assessment of Morus alba samples

Abstract: High-performance thin-layer chromatography/bioautography and and liquid chromatography-mass spectrometry hyphenated with chemometrics for the quality assessment of Morus alba samples,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 22 publications
0
8
1
Order By: Relevance
“…In the case of gallic acid, the results obtained in this study were higher, while for vanillic, caffeic and p -coumaric acids, the results obtained were slightly lower on comparing with the results obtained by Flaczyk et al [31]. This could be explained by the differences in the growing conditions in different regions [32]. Moreover, a literature screening also revealed that the efficiency of phenolic extraction depends on the extraction method, solvent type and drying process used for the plant material [28].…”
Section: Resultscontrasting
confidence: 55%
“…In the case of gallic acid, the results obtained in this study were higher, while for vanillic, caffeic and p -coumaric acids, the results obtained were slightly lower on comparing with the results obtained by Flaczyk et al [31]. This could be explained by the differences in the growing conditions in different regions [32]. Moreover, a literature screening also revealed that the efficiency of phenolic extraction depends on the extraction method, solvent type and drying process used for the plant material [28].…”
Section: Resultscontrasting
confidence: 55%
“…For visualization, the bioautogram was immersed into a solution of MTT dye with Triton X-100 (1 mg/mL). To enhance the intensity of the yellow bands, one drop of Triton X-100/10 mL MTT aqueous solution was added (Ristivojević et al, 2018;Ristivojević, Tahir, Malfent, Milojkovic, Opsenica & Rollinger, 2019). The obtained bioautograms were documented using TLC Visualizer 2 under white light.…”
Section: Hptlc-bioautography Antimicrobial Assaysmentioning
confidence: 99%
“…After derivatization with DPPH solution (1 mg/mL), the plate was dried for 90 s in the dark at ambient temperature. Then, the obtained bioautogram was documented every 3 min for 30 min using TLC Visualizer 2 under white light (Ristivojević et al, 2018;Ristivojević et al, 2019).…”
Section: Hptlc-bioautography Dpph Assaymentioning
confidence: 99%
“…It can not only show the activity of the herbal drugs but also reveal which components contribute to the activity. Due to the merits of being simple, convenient and requiring no laborious isolation, TLC-bioautography has been widely employed for screening and identification of herbal drugs components with bioactivity such as anti-microbial [ 42 ], acetylcholinesterase inhibition [ 43 , 44 ], α- and β-glucosidase inhibition [ 45 , 46 ], free radical scavenging and antioxidation [ 42 , 47 ]. Actually, ChP has already included TLC-bioautography against 2,2-diphenyl-1-picrylhydrazyl radical for the identification of Rehmanniae Radix.…”
Section: Advanced Analytical Techniques For Quality Standard Of Tcmmentioning
confidence: 99%